Restoring functional integrity of the global production ecosystem through biological control - Wyckhuys, Kris A.G.; Gu, Baogen; Fekih, Ibtissem Ben; Finger, Robert; Kenis, Mark; Lu, Yanhui; Subramanian, Sevgan; Tang, Fiona H.M.; Weber, Donald C.; Zhang, Wei; Hadi, Buyung A.R. (Elsevier, 2024)
Human society is anchored in the global agroecosystem. For millennia, this system has provided humans with copious supplies of nutrient-rich food. Yet, through chemical intensification and simplification, vast shares of present-day farmland derive insufficient benefits from biodiversity and prove highly vulnerable to biotic stressors. Here, we argue that on-farm action centered on biological control can effectively defuse pest risk by bolstering foundational ecosystem services. By harnessing plant, animal and microbial biodiversity, biological control offers safe, efficacious and economically-sound plant health solutions and coevolved options for invasive species mitigation. In recent years, its scientific foundation has been fortified and solutions have been refined for myriad ecologically brittle systems. Yet, for biological control to be mainstreamed, it needs to be rebooted, intertwined with (on- and off-farm) agroecological tactics and refurbished - from research, policy and regulation, public-private partnerships up to modes of implementation. Misaligned incentives (for chemical pesticides) and adoption barriers further need to be removed, while its scientific underpinnings should become more interdisciplinary, policy-relevant, solution-oriented and linked with market demand. Thus, biological control could ensure human wellbeing in a nature-friendly manner and retain farmland ecological functioning under global change.